2019
DOI: 10.1007/s10584-019-02592-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeled gradual changes in protein intake to increase nutrient adequacy lead to greater sustainability when systematically targeting an increase in the share of plant protein

Abstract: This is the "postprint" version, i.e. the authors' version that has been accepted for publication, of the article by De Gavelle et al., finally published in Climatic Change in 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For instance, in the NutriNet-Santé study also conducted in France, we have already shown that it is possible to reduce GHGe by 50% from the nutritionally adequate diets by reducing and rearranging the consumptions of animal products while ensuring nutritional adequacy (28). Smaller changes in protein intake in favor of plant protein targeting an increase in nutrient adequacy also decrease GHGe (29).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the NutriNet-Santé study also conducted in France, we have already shown that it is possible to reduce GHGe by 50% from the nutritionally adequate diets by reducing and rearranging the consumptions of animal products while ensuring nutritional adequacy (28). Smaller changes in protein intake in favor of plant protein targeting an increase in nutrient adequacy also decrease GHGe (29).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is clear that a protein transition is needed to achieve more environmentally-friendly diets [ 19 , 22 , 49 ]. To increase protein intake in an environmentally friendly way in older adults, the diet optimization study showed that a shift towards a more plant-based diet was needed, one in which the animal- to plant-protein ratio shifts from 60:40 to 50:50 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously argued that increasing protein intake based on current food consumption patterns is likely to have unfavorable consequences for the natural environment [18][19][20]. Globally, current food production and consumption are dominant drivers of climate change, eutrophication (excessive richness of nutrients in water), acidification (water or soil becomes too acid), and biodiversity loss and are a considerable drain on resources such as land, water, energy, and nutrients [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…25 Similarly, a French study showed that step-by-step substitutions of animal protein sources by plant protein sources in order to improve nutritional quality without upsetting the habits of each participant would decrease the carbon footprint only of their diets by 5%. 47 Main conclusions from studies using approach 1…”
Section: Advantages and Limitations Of The Analysis Of Hypothetical Diets Based On Predetermined Assumptionsmentioning
confidence: 99%